The development of a decision aid for shared decision making in the Dutch implantable cardioverter defibrillator patient population: A novel approach to patient education - Yilmaz, Dilek; Egorova, Anastasia D.; Schalij, Martin J.; Spierenburg, Han A. M.; Verbunt, Robert A. M.; van Erven, Lieselot (Frontiers in Cardiovascular Medicine, 2022)
Background Counseling of Implantable Cardioverter-defibrillator (ICD) patients with regard to individual risks and benefits is challenging. An evidence-based decision aid tailored to the needs of Dutch ICD patients is not yet available. The objective of this pilot project was to structurally evaluate the current clinical practice in The Netherlands and the ICD patient experience, in order to develop an online decision aid to facilitate shared decision making in ICD procedures. Methods Between June 2016 and December 2017, a Dutch web-based decision aid was developed according to the Patient Decision Aid Standards (IPDAS) using the RAND-UCLA/multi-stepped Delphi model. Development process consisted of 5 stages in which the Dutch clinical practice was reviewed (stage 1), patients’ needs and their history of decision making was structurally assessed (stages 2A and B) and a modified Delphi consensus process was performed with an expert panel consisting of representatives from different medical fields (stage 3). Results from stages 1–3 were used to design and structure the content of an online-based decision aid (stage 4) which was finally evaluated in a usability testing by patients in stage 5. Results and conclusion This study describes the evidence-based approach to the development of the Dutch ICD decision aid. In our population, levels of shared decision-making experience were low. The ICD decision aid was structurally developed for the Dutch ICD patient population. Our upcoming multicenter stepped wedge clustered randomized trial will further evaluate the ICD decision aid in clinical practice.